Peningkatan Keterampilan dan Kompetensi Siswa SMK dalam Menghadapi Era Revolusi Industri 4.0 melalui Pelatihan 3D Printing - Sigit Mujiarto; Ikhwan Taufik; Muhammad Ja'far Ahsinul Rokhmat; Nurbaity Khoirun Nissa; Mohammad 'Ulyan (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The Industrial Revolution 4.0 requires Vocational High Schools (SMK) to master key technologies such as 3D Printing. SMK Negeri 1 Windusari, the service partner, faces technology gaps, characterized by limited equipment and a lack of practical (hands-on) knowledge regarding FDM 3D Printing. The objective of this service is to enhance the knowledge and understanding of students, teachers, and lab assistants regarding 3D Printing (Additive Manufacturing) as a core pillar of Industry 4.0. The methodology involved integrating knowledge transfer and practical skills (learning by doing) using FDM machines. The service emphasized a participatory and community-driven relevance approach. Evaluation was conducted quantitatively using pre-test and post-test comparisons. Results showed a significant increase in competence, with the participants’ average score rising from 50.67 to 74. This strengthens the competence of the Machining Engineering Department, preparing adaptive graduates in the field of Additive Manufacturing.